Desenvolvimento de métodos moleculares e sorológicos para diagnóstico específico de infecções por Leishmania (Leishmania) amazonensis - Jordanna Luíza de Lima Celeste (2019)
The wide distribution and overlapping of Leishmania species and different clinical forms of leishmaniasis in the country can directly affect the clinical course of the disease, diagnosis, control and treatment. Thereby, the development of species-specific diagnostic methods that can be used routinely are necessary and of great importance. In Brazil, Leishmania amazonensis is an etiological agent mainly of the cutaneous form of the disease, but has already been found promoting visceral disease in humans and dogs. In addition, its coexistence with other species of the parasite, such as L. infantum, etiological agent of visceral leishmaniasis, makes it very important to identify the species during the diagnosis of Leishmania spp. For this, in the present work, as molecular test, we standardized the LAMP (Loop-Mediated Isothermal Amplification) technique, with the design and use of specific primers for L. amazonensis and visualization of the result using polyacrylamide gel and colorimetric detection (SYBR® Safe). The reaction showed 100% specificity when compared L. infantum, L. braziliensis, L. major, L. mexicana, L. donovani, L. guyanensis, Trypanosoma cruzi, Babesia canis and Toxoplasma gondii species and when tested different strains of L. amazonensis. The detection limit of the reaction was 10pg of L. amazonensis DNA. It presented 89% sensitivity when compared to conventional PCR using hamster skin DNA samples experimentally infected with L. amazonensis (n=9), L. infantum (n=9) and coinfection (n=9). For the development of a serological test, an immunoproteomic approach was used to select species-specific antigenic proteins. For this, we used protein extract of L. amazonensis fractionated in bi-dimensional electrophoresis (2-DE) and western blot (WB) with pool of hamster sera experimentally infected with L. amazonensis and L. infantum. The overlap between 2-DE gel images and WB membranes allowed the selection of 8 spots reactive only to sera from animals infected with L. amazonensis and not reactive to sera from L. infantum or uninfected. Two proteins were identified in 6/8 spots. One of them, the recombinantly produced HSP-70 was used as an antigen in an ELISA test with pool of hamsters sera infected with L. amazonensis, L. infantum, coinfected and uninfected. There was a significant difference (P<0.05) only when the infected groups were compared to the uninfected control, not being a species-specific antigen.